PHYTOCHEMICAL PROFILE, IN VITRO ANTI-DIABETIC POTENTIAL VIA ENZYME INHIBITION ASSAYS, AND IN VIVO ANTI-HYPERGLYCEMIC EFFECTS OF THE HYDRO-ALCOHOLIC EXTRACT OF Bombax ceiba FLOWERS IN A STREPTOZOTOCIN (STZ)-INDUCED DIABETIC RAT MODEL. - Brijesh Kumar Saroj; Rajendra Madhukar Kawade; Umadevi. A; Sonu Sharma; Suman Lata Mehta; Ritesh Kumar; Satya Narayan Sahu; Tapan Kumar Sahu (The Bioscan, 2025)
Traditional Asian medicine makes extensive use of the Silk Cotton Tree, scientifically known as Bombax ceiba L. (Malvaceae). Maceration was used to extract the Bombax ceiba flowers with 70% ethanol. We conducted both qualitative and quantitative studies of phytochemicals. We used alpha-amylase and alpha-glucosidase inhibition experiments, with acarbose as the standard, to evaluate the in vitro anti-diabetic potential. In the in vivo experiment, Wistar rats were administered 55 mg/kg of STZ intraperitoneally to induce diabetes. For 28 days, diabetic rats were given oral doses of 200 mg/kg and 400 mg/kg body weight of BCFE, with 5 mg/kg of Metformin serving as the standard medication. Results: Phytochemical analysis identified phenols, steroids, tannins, and saponins. The content of total phenolics was determined to be 98.5 ± 3.2 mg GAE/g, whereas the content of flavonoids was 65.4 ± 2.1 mg QE/g of extract. BCFE showed a similar pattern to acarbose in inhibiting alpha-amylase (IC50: 112.4 μg/mL) and alpha-glucosidase (IC50: 85.7 μg/mL), with the effects increasing with increasing dose. The effects of BCFE treatment on diabetic rats were dosage-dependently lowered FBG and HbA1c levels, improved blood insulin and lipid profiles, and comparable to metformin at a dose of 400 mg/kg, according to the in vivo investigation (p < 0.001). Conclusion: The findings lend credence to the long-standing practice of using Bombax ceiba flowers for medicinal purposes. The anti-diabetic effects are most likely caused by the high levels of phenolic and flavonoid compounds found in it. These compounds have the ability to inhibit enzymes that break down carbohydrates and may even stimulate the regeneration of pancreatic beta cells or the release of insulin. As a powerful natural supplement for diabetic treatment, BCFE has great potential.